The Study of Urban Governance in Taipei City (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of this study is to examine the impact of urban governance on public sector performance by observing the urban governance practices of the Taipei City. The study shows that since 2014, Taipei City has promoted urban governance in a performance-oriented manner, and after 8 years of efforts, it has achieved the overall synergy of an international metropolis. The urban governance practice of Taipei City takes becoming a livable city as its vision and goal, and uses the Balanced Scorecard as an implementation tool. The results show that, according to The Economist’s 2018 ranking of the top 100 livable cities in the world, Taipei City has entered the top 60, and will advance to 33 in 2021. The performance of urban governance is quite remarkable.